2016
DOI: 10.1098/rsbl.2016.0648
|View full text |Cite
|
Sign up to set email alerts
|

Social-bond strength influences vocally mediated recruitment to mobbing

Abstract: Strong social bonds form between individuals in many group-living species, and these relationships can have important fitness benefits. When responding to vocalizations produced by groupmates, receivers are expected to adjust their behaviour depending on the nature of the bond they share with the signaller. Here we investigate whether the strength of the signaller-receiver social bond affects response to calls that attract others to help mob a predator. Using field-based playback experiments on a habituated po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 22 publications
3
51
0
Order By: Relevance
“…Although the level of correct classification for all three calls types was relatively low when compared to that of other studies (Briseño‐Jaramillo, Estrada, & Lemasson, ; Collins et al., ; Gillam & Chaverri, ; Leliveld et al., ), the PIC values were comparatively high (e.g., Bouchet et al., ; Salmi, Hammerschmidt, & Doran‐Sheehy, ). Previous research has shown that dwarf mongooses are capable of discriminating between individuals for each of the three call types (Kern & Radford, ; Rubow et al., ; Sharpe et al., ), suggesting that high levels of call individuality are not a necessity for individual recognition and discrimination. For example, although banded mongoose escort contact calls achieved low correct classification percentages, the acoustic distinction was sufficient to allow mongoose pups to discriminate between individual callers (Müller & Manser, ).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Although the level of correct classification for all three calls types was relatively low when compared to that of other studies (Briseño‐Jaramillo, Estrada, & Lemasson, ; Collins et al., ; Gillam & Chaverri, ; Leliveld et al., ), the PIC values were comparatively high (e.g., Bouchet et al., ; Salmi, Hammerschmidt, & Doran‐Sheehy, ). Previous research has shown that dwarf mongooses are capable of discriminating between individuals for each of the three call types (Kern & Radford, ; Rubow et al., ; Sharpe et al., ), suggesting that high levels of call individuality are not a necessity for individual recognition and discrimination. For example, although banded mongoose escort contact calls achieved low correct classification percentages, the acoustic distinction was sufficient to allow mongoose pups to discriminate between individual callers (Müller & Manser, ).…”
Section: Discussionmentioning
confidence: 94%
“…The dwarf mongoose's snake call also serves a recruitment function, with receivers initially searching for the snake and then banding together to mob the reptile (Rubow et al., ). Individuals are known to respond more strongly to the snake calls of companions (those with whom they most often allo‐groom and forage; Kern & Radford, ), but a signaler is unlikely to benefit directly from receiver response (regardless of its strength) because it is not at risk (i.e., it knows the snake's location, and snakes only catch dwarf mongooses if they can take them unawares; L. L. Sharpe, personal observation).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations